KARAKTERISTIK DAN PEMILIHAN POHON TIDUR BURUNG NURI TALAUD (Eos histrio Muller, 1776) DI PULAU KARAKELANG - KEPULUAN TALAUD SULAWESI UTARA - , Diah Irawati Dwi A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aimed to identify factors that strongly influenced the selection of roosting tree by the Red and Blue Lories birds and to estimate their recent population using roost survey method. The study lasted for four months at Karakelang Island. The location distribution was obtained from direct observation and from the previous reports described on map using GIS. The data were analyzed using descriptive statistic method, T-test, Mann-Whitney test, Chisquare test and Logistic Regression. The results showed that eleven roosting trees were found. Among them, six trees were still being used by the birds but the others had been abandoned. From the results of the location distribution, Ammat and Binalang villages had the highest number of roosting trees (3). Four kinds of roosting trees were identified